The Komunikasi Partisipatif Antara Sekolah Dan Keluarga Dalam Pendidikan Anak Usia Dini di RA At Thoriq Batam: Chidhood Education - Darma, Darmawati; Maya Inayati Sari; Yuli Fatimah Warosari; Nurhayati (Institut Agama Islam Negeri Madura, 2024)
Early childhood education plays a crucial role in shaping a child's developmental foundation. In an effort to understand how early childhood education can be enhanced, this research delves into the theme of